A Monodispersed Spherical Zr‐Based Metal–Organic Framework Catalyst, Pt/Au@Pd@UIO‐66, Comprising an Au@Pd Core–Shell Encapsulated in a UIO‐66 Center and Its Highly Selective CO2 Hydrogenation to Produce CO. Issue 5 (4th December 2017) - Zheng, Zhizhong; Xu, Haitao; Xu, Zhenliang; Ge, Jianping
Abstract: A Zr‐based metal–organic framework (MOF) catalyst, Pt/Au@Pd@UIO‐66, is assembled, where UIO‐66 is Zr6 O4 (OH)4 (BDC)6 (BDC = 1, 4‐benzenedicarboxylate). The gold nanoparticles (NPs) act as the core for the epitaxial growth of Pd shells, and the core–shell monodispersed nanosphere Au@Pd is encapsulated into UIO‐66 to control its morphology and impart nanoparticle functionality. The microporous nature of UIO‐66 assists the adsorption of Pt NPs, which in turn enhances the interaction between NPs and UIO‐66, favoring the formation of isolated and well‐dispersed Pt NP active sites. This MOF exhibits high catalytic activity and CO product selectivity for the reverse‐water–gas‐shift reaction in a fixed‐bed flow reactor. Abstract : A Zr‐based metal–organic framework catalyst Pt/Au@Pd@UIO‐66 was assembled. The gold nanoparticles act as the core for the epitaxial growth of Pd shells, and the core–shell Au@Pd encapsulated into UIO‐66 controls its morphology and imparts nanoparticle functionality. This monodispersed catalyst exhibits high catalytic activity and CO product selectivity for the reverse‐water–gas‐shift reaction.